An Applied Guide to Process and Plant Design - Moran, Seán (Chemical engineer) (Butterworth-Heinemann, 2015)
An Applied Guide to Process and Plant Design is a guide to process plant design for both students and professional engineers. The book covers plant layout and the use of spreadsheet programmes and key drawings produced by professional engineers as aids to design; subjects which are usually learned on the job rather than in education. You will learn how to produce smarter plant design through the use of computer tools, including Excel and AutoCAD, "What If Analysis", statistical tools, and Visual Basic for more complex problems. The book also includes a wealth of selection tables, covering the key aspects of professional plant design which engineering students and early-career engineers tend to find most challenging. Professor Moran draws on over 20 years' experience in process design to create an essential foundational book ideal for those who are new to process design, compliant with both professional practice and the IChemE degree accreditation guidelines.
Includes index.
Keywords: Factories -- Design and construction.; Production engineering.; elektronické knihy; electronic books